Kit "Energy, Environment and Sustainability": An Educational Strategy for a Sustainable Future. A Case Study for Guinea-Bissau - Joana Oliveira; Luísa Neves; Senentxu Lanceros-Mendez (MDPI AG, 2021)
Increasing the scientific knowledge of the population through education is a development strategy towards a sustainable future. However, there is no equity in the access to science education and scientific knowledge. The aim of this paper is to present and analyse a science kit named "Energy, Environment and Sustainability" (KEAS). Based on research conducted in Guinea-Bissau, it explores strategies to promote science education for a sustainable future. The strengths and limitations of the KEAS were studied using different data collection methods, including interviews, observation, survey, focus groups and document analysis. The participants were teacher trainers from the Guinea-Bissau School of Education. It is concluded that the KEAS is a feasible and suitable teaching strategy appropriate to the context, having the potential to contribute to learning about the environment and sustainability. Further, it addresses real problems for which students should acquire knowledge and skills in order to be able to make informed choices.